Structure and characterization of an Urban forest fragment in Tubarão, Santa Catarina, Brazil Estrutura e Caracterização de um Fragmento Florestal Urbano em Tubarão, Santa Catarina, Brasil - Turmina E.* (2017)
© 2017. revistaESPACIOS.com.The aim of this study was to characterize a forest fragment by phytosociological descriptors and classify the successional stage by the CONAMA resolution 4 from 05/04/94. The survey was conducted in Tubarão municipality, SC in urban areas, using full inventory. All arboreal individuals with breast height diameter - 1.30 ≥ four were collected, identified and measured (CAP - and estimated height). The horizontal structure, Shannon-Wiever index (H') and equability of Pielou (J) was calculated. The characterization by Resolution no 4/94 was carried by DAP medium values, height, basal area and indicator species. Were registered 148 arboreal individuals, distributed in 15 families and 14 genus. Alchornea glandulosa Poepp. & Endl (Tanheiro) and Syagrus romanzoffiana (Cham.) Glassman (Jerivá) stood out for having the most representative values of these descriptors and IVC's. fragment was defined as Secondary Vegetation in Medium Regeneration Stage and has a high diversity of species.